2023
DOI: 10.1101/2023.01.22.23284882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Performance of ChatGPT in Ophthalmology: An Analysis of its Successes and Shortcomings

Abstract: We tested the accuracy of ChatGPT, a large language model (LLM), in the ophthalmology question-answering space using two popular multiple choice question banks used for the high-stakes Ophthalmic Knowledge Assessment Program (OKAP) exam. The testing sets were of easy-to-moderate difficulty and were diversified, including recall, interpretation, practical and clinical decision-making problems. ChatGPT achieved 55.8% and 42.7% accuracy in the two 260-question simulated exams. Its performance varied across subspe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(189 citation statements)
references
References 14 publications
5
121
1
2
Order By: Relevance
“…Its answers were verified and compared against the extant literature. These results are like those reported in other subjects, including law (Choi et al, 2023), mathematics (Frieder et al, 2023), and specialized medicine, such as ophthalmology (Antaki et al, 2023). Overall, ChatGPT's academic performance was mediocre.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Its answers were verified and compared against the extant literature. These results are like those reported in other subjects, including law (Choi et al, 2023), mathematics (Frieder et al, 2023), and specialized medicine, such as ophthalmology (Antaki et al, 2023). Overall, ChatGPT's academic performance was mediocre.…”
Section: Discussionsupporting
confidence: 82%
“…However, the developers at OpenAI warn users about the model's shortcomings and explicitly state that sometimes it can come up with inadequate, or even nonsensical, answers. Therefore, the results obtained in sports science and psychology in this research, like in other academic subjects (Antaki et al, 2023;Choi et al, 2023;Frieder et al, 2023), could be anticipated. While in the course of its further development, ChatGPT will likely perform better, in agreement with Hanna (2023) it won't perform miracles as it uses existing information.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Specifically, in ophthalmology examination, Antaki et al showed that ChatGPT currently performed at the level of an average first-year resident [ 70 ]. Such a result highlights the need to focus on questions involving the assessment of critical and problem-based thinking [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ChatGPT also shapes cultural norms and values by feeding back into society and individuals' embodied experiences. In fact, it is today raising enormous concerns in education (Alshater, 2022) and specialized work areas (Kung et al, 2022;Guo et al, 2023;Antaki et al, 2023). In summary, ChatGPT as a language model can be seen as a product of both biology and culture, as it is informed by our understanding of natural language processing and driven by the needs and priorities of human society.…”
Section: Preprint -Please Cite the Originalmentioning
confidence: 99%